Three-Qubit Quantum System Classification Method Using Special Linear Group Under Stochastic Local Operations and Classical Communication ( SLOCC) Protocol - Amirul Asyraf bin Mohamad Zhahir (Universiti Sains Islam Malaysia, 2024)
Matric: 3211381(FST) -Restricted until Jan' 27